Suitability Study of Ag Nanosheet Sers Substrates as a Screening Method for Imidacloprid After Quechers Extraction - Ruiz-Leon, D; Ruiz-Leon, D (Royal Society of Chemistry, 2024)
With the current food demand, pesticides have become some of the most important compounds to maintain food quality; however, this requires the development of methodologies that allow fast, sensitive, and low-cost screening for these contaminants. Surface-enhanced Raman spectroscopy is an emerging solution since the interaction between the analyte and metallic nanostructures increases the Raman signals, enabling trace detection and a chemical-specific measurement. In this way, the fast detection of contaminants is possible, and further advances may enable portable assays. In this work, SERS substrates with silver nanosheets (AgNSs) on a copper surface were synthesized, producing a strong SERS effect and a reproducible signal intensity from methylene blue probe molecules at an optimal reaction time of 1 min. A quantitative analysis of the pesticide imidacloprid was then performed by applying a PLSR chemometric model, revealing a high linear correlation between the reference values and the predicted values of the pesticide (Rcv2 = 0.9732 and RMSECV = 0.1239). AgNS substrates were used to determine the feasibility of using this methodology for screening imidacloprid in real bee honey samples obtained through QuEChERS extraction, and an average recovery of 75.5% ± 0.08 was obtained. In addition, density functional theory simulations were carried out to elucidate the possible molecular interaction with the SERS surface and to assign the observed vibrational modes of imidacloprid. SERS is thus demonstrated to be an alternative to conventional pesticide detection techniques. This journal is © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2024.